Implementasi Pembelajaran Berbasis Multikultural di Sekolah Dasar - Romadon, Muhammad; Marini, Arita; Maksum, Arifin (Jurnal Basicedu, 2021)
This research is about the description of the implementation of multicultural-based learning. The results of this study indicate the implementation of multicultural-based learning in elementary schools of SDN Menteng 03 Pagi South Jakarta, namely 1) learning is carried out, 2) creating a pleasant learning atmosphere, 3) using various learning methods, 4) implementing learning media using laptops and learning facilities according to student needs, 5) showing learning outcomes, 6) establishing cooperation between teachers and parents. Meanwhile, the main factor supporting teachers in order to provide effectiveness of multicultural-based learning is by utilizing facilities that support learning and learning facilities. Then the main factor that makes multicultural-based learning very good is the collaboration between teachers and parents. The research method used is data triangulation, namely teacher respondents, school principals and students.